The evolution of tools for protein phosphorylation site analysis: from discovery to clinical application. (April 2008) - Bonilla, Leo E.; Means, Gary D.; Lee, Kimberly A.; Patterson, Scott D.
The importance of the analysis of signaling pathways has been proven for many years by the elucidation of key signaling molecules. However, in most cases these pathways tend to represent a rather narrow view of the biological state under investigation. Clearly a more detailed understanding of the complexities of cross-talk between signaling pathways is required to further our knowledge of normal and disease processes. The tools that provide the framework for this increased understanding of biology, those that enable identification, characterization, and quantitation of sites of phosphorylation in proteins, have advanced over the past 25 years. This review will present a brief overview of the history of the tools used in phosphorylation analysis and the latest technologies that are being applied in this field, such as mass spectrometry (for broad-based discovery efforts) and flow cytometry (for translation to clinical applications).